Lutein-Containing Antioxidants in Patients with Primary Open-Angle Glaucoma and Dry Type of Age-Related Macular Degeneration - D. A. Dorofeev (Oftalʹmologiâ, 2018)
Objective. To assess the dynamics of structural-functional markers in patients with combined pathology: primary open-angle glaucoma (POAG) and age-related macular degeneration (AMD) with the background of lutein-containing drugs at long-term follow-up. Patients and Methods. The period of research was from November 2016 to January 2018; A parallel prospective study of patients (88 eyes), mean age 67.81 ± 8.41 (M ± σ); 67.64 (63.14; 73.08) (Me, Q25%, Q75%) years with combined pathology POAG and AMD (AREDS I and II). Patients were divided into 2 groups, the first group — a study group received Retinorm, by 1 capsule 3 times a day during a meal for 1 year, a second control group of 17 patients (32 eyes) did not receive lutein-containing medicines during the observation period. The study group consisted of 29 patients (55 eyes). There were 7 males and 22 females among them. The control group consisted of 19 patients (33 eyes), 2 males and 17 females among them. Visual acuity, standard automatic computer perimetry, optical coherence tomography, determination of spatial contrast sensitivity was carried out in all patients at the beginning of the study and after 1 year. Results. The maximum correlated visual acuity (MCVA) according to the table ETDRS increased in the study group and decreased in the control group, 95% the confidence interval for the changes in the MCVA: 0.1813636; 1.018182; 1.927273 и –3.878788; –2.393939; –0.8477273 (optotypes), respectively (W = 499.5; p = 0,0002919). Statistically significant changes in the thickness of the layer of nerve fibers of the retina (RNFL) neither in the middle nor in the sectors was revealed, and the thickness of the retina in oval foveal zone by sector: upper, temporal and lower statistically significantly decreased in the control group, while remaining unchanged in the observation group (р < 0.05). Spatial contrast sensitivity (SCS) after 1 year of use Retinorm remained at the same level in the control group, while there was a statistically significant increase in spatial contrast sensitivity in the main group, especially at high spatial frequencies is observed (р < 0.05). Conclusion. The results of the study indicate a positive effect of Retinorm used for 1 year. It was reflected in the improvement visual acuity in the distance, improvement of spatial contrast sensitivity, especially at high spatial frequencies, and the preservation of structural retinal indices both in the foveal zone and peripapillary.